2005
DOI: 10.5380/pes.v15i0.4468
|View full text |Cite
|
Sign up to set email alerts
|

Ecogenotoxicologia Dos Agrotóxicos: Avaliação Comparativa Entre Ecossistema Agrícola E Área De Proteção Ambiental

Abstract: Mesmo que se dê um passo apenas pode se sentir uma razão de viver, iluminada pela ' Esperança de Vencer '.Ao meu esposo, Celso, quem sempre me apoiou nessa e em outras jornadas.A minha mãe, meu pai e minha irmã, que mesmo distante, mantiveram-se sempre ao meu lado.Dedico mais esta conquista, com a mais profunda admiração e respeito. Ao orientador Prof. Dr. César Koppe Grisólia e à "ex-orientadora" Dra. IrisFerrari, pela dedicação à pesquisa, apoio no desenvolvimento do nosso trabalho e principalmente pelo ince… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
0
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
2
0
0
3
Order By: Relevance
“…This was probably the result of differences in the selective pressures applied to the field and experimental populations. The study of Rodrigues et al (2005) supports our proposal regarding the adaptability of allele Est3-3 in environments exposed to insecticides. In their study, these authors found a higher frequency of allele Est3-3 in Z. indianus populations exposed to insecticides (0.193 in unexposed areas, and 0.266 in areas where the insecticide had been applied) in Campo Verde (Mato Grosso State, Brazil), a locality that has a history of agriculture and insecticidal pest control.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This was probably the result of differences in the selective pressures applied to the field and experimental populations. The study of Rodrigues et al (2005) supports our proposal regarding the adaptability of allele Est3-3 in environments exposed to insecticides. In their study, these authors found a higher frequency of allele Est3-3 in Z. indianus populations exposed to insecticides (0.193 in unexposed areas, and 0.266 in areas where the insecticide had been applied) in Campo Verde (Mato Grosso State, Brazil), a locality that has a history of agriculture and insecticidal pest control.…”
Section: Discussionsupporting
confidence: 86%
“…This was probably the result of differences in the selective pressures applied to the field and experimental populations. The study of Rodrigues et al. (2005) supports our proposal regarding the adaptability of allele Est3‐3 in environments exposed to insecticides.…”
Section: Discussionsupporting
confidence: 86%
“…É banhado pelos rios São Lourenço, Rio das Mortes, Aricá Mirin, Cumbica, Roncador, Ximbica, Galheiros e da Casca. Sua economia provém Variação espaço-temporal na abundância de ordens e famílias... de diversos setores, sendo o plantio de soja (75.000ha), algodão (60.416ha) e milho (26.000ha) que colocam o município em destaque nacional (RODRIGUES et al, 2005).…”
Section: Methodsunclassified
“…Dentre as biomarcas mais utilizadas para avaliações de respostas ambientais/laboratoriais, está o ensaio do micronúcleo (MN), que foi inicialmente proposto como um teste para detecção de agentes carcinogênicos em células de medula óssea de camundongo (Cabrioti, 2005). Posteriormente vários protocolos foram desenvolvidos aplicando o teste em outros organismos e em linhagens celulares diversas, tais como humanos, roedores, anfíbios, peixes, moluscos bivalves, ouriços e plantas (Venier et al, 1997;Fenech, 2000;Ribeiro, 2003;Rodrigues et al, 2005;Carvalho, 2005). O bioensaio de MN teve rápida aceitação como bioindicador da qualidade dos ecossistemas aquáticos, especialmente com o uso de peixes, devido principalmente à padronização da técnica, rápidos resultados e fácil adaptação para estudos in situ.…”
Section: Introductionunclassified